2020
DOI: 10.1039/c9sc06140a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic resonance theory: parallel reaction pathway control

Abstract: Branched catalytic reaction networks with oscillating chemical pathways perfectly select for reaction products at varying frequency.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 49 publications
4
50
1
Order By: Relevance
“…Although not shown here, sampling of a wider range of both chemical and dynamic catalyst parameters indicates significant potential for controlling the selectivity to products for a wide range of catalytic chemistries. (51)…”
Section: Rate Of Conversion Of a Tofmentioning
confidence: 99%
See 3 more Smart Citations
“…Although not shown here, sampling of a wider range of both chemical and dynamic catalyst parameters indicates significant potential for controlling the selectivity to products for a wide range of catalytic chemistries. (51)…”
Section: Rate Of Conversion Of a Tofmentioning
confidence: 99%
“…As shown in Figure 17a, comparison of the periodic trends for the adsorption of NH 2 * and NH* with the application of electric fields on Pt (111) surface both indicate positive scaling of NH2 * /NH * of 0.49 and 1.37, respectively. (51,276,(312)(313)(314)(315)(316)(317) The divergence of the two linear relations indicates the potential for breaking periodic linear scaling relationships. In addition, the linear relationships (i.e., gamma parameters) are likely to be metaldependent for the same external stimulus, as shown for distinct CH2O2 * * /CH3OH * on Ni (111) and Pt (111) surface (Figure 17b).…”
Section: Evaluating Catalytic Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%